HER2 Gene Protein Assay: A Robust Tool for Evaluating HER2 Status and Intratumoral Heterogeneity in Endometrial Cancers. Issue 5 (1st March 2023) - Shafi, Saba; Nitta, Hiroaki; Shah, Manan; Challa, Bindu; Parwani, Anil V; Li, Zaibo
Abstract: Objectives: Human epidermal growth factor receptor 2 (HER2) status in endometrial cancer is usually determined by immunohistochemistry and/or in situ hybridization. We employed a novel HER2 gene protein assay (GPA) to simultaneously assesses HER2 gene amplification and protein expression in high-grade endometrial cancers. Methods: We performed GPA in 180 endometrial cancers, including 106 serous carcinomas, 34 carcinosarcomas, and 40 mixed epithelial carcinomas. HER2 status was determined using the 2018 HER2 guidelines for breast carcinoma, and HER2 intratumoral heterogeneity (ITH) was examined. Clinicopathologic characteristics were collected and correlated with HER2 status. Results: HER2 positivity was noted in 32% of serous carcinomas, significantly higher than in carcinosarcomas (5.9%) and mixed carcinomas (12.5%). HER2 ITH was detected in 32% of serous carcinomas, significantly greater than in carcinosarcomas (8.8%) and mixed carcinomas (10%). Patients with carcinosarcoma had a significantly lower overall survival than patients with serous or mixed epithelial carcinoma, but HER2 status caused no difference in survival in patients with serous carcinoma. Conclusions: HER2 GPA can be used to accurately determine HER2 status in endometrial cancers and is a highly valuable tool for identifying HER2 heterogeneity.